The Actualization of Tazkiyatun Nafs Values in The Moral Development of Students of The Ulul Albab Islamic Studies Organization (KSI) UIN Padang - Gusmi Ranti; Jamaldi Jamaldi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This study focuses on examining the actualization of the values of Tazkiyatun Nafs in the moral development of the students of the KSI Ulul Albab organization UIN Imam Bonjol. The thought of Imam Al-Ghazali and other scholars about the tazkiyatun nafs is very interesting and important to apply as a moral basis in developing the morals of the people, especially the development of the younger generation. By using descriptive qualitative research by conducting interviews with students who are active in KSI, it is concluded that the actualization of the values of tazkiyah al-nafs in building morals and religious character in instilling noble souls and having al-karimah character. then from the application of the values of tazkiyah al-nafs it also includes a strategy in the habituation of students of the KSI Ulul Albab organization in the hope of creating student discipline and changing bad morals or being therapy for bad souls into good morals. Even the application of tazkiyah al-nafs values in the form of mental therapy. Tazkiyah al-nafs in the form of mental therapy is based on the argument that the human soul can be treated. Efforts to treat mental illness must be done through science and charity. Science here serves to determine the cause and effect of a mental illnessPenelitian ini mengkaji tentang aktualisai nilai-nilai Tazkiyatun Nafs dalam pembinaan akhlak mahasiswa organisasi KSI Ulul Albab UIN Imam Bonjol. Pemikiran Imam Al-Ghazali dan ulama lain tentang tazkiyatun nafs tersebut diterapkan sebagai landasan moril dalam pengembangan akhlak umat teritama pembinaan generasi muda. Dengan menggunakan penelitian kualitatif deskriptif, peneliti melakukan wawancara dengan mahasiswa yang aktif dalam KSI serta mengamati kegiatan mereka. Sehingga dapat disimpulkan bahwa aktualisasi nilai-nilai tazkiyah al-nafs dilakukan melalui pembinaan akhlak dan karakter religious dalam menanamkan jiwa-jiwa yang mulia dan berakhlaq al-karimah. Penerapan nilai-nilai tazkiyah al-nafs itu juga termasuk strategi dalam pembiasaan mahasiswa organisasi KSI Ulul Albab dengan harapan tercipta suatu kedisiplinan mahasiswa dan perubahan akhlak yang buruk atau menjadi terapi bagi jiwa yang buruk menjadi akhlak yang baik. Bahkan penerapan nilai-nilai tazkiyah al-nafs dalam bentuk terapi jiwa. Tazkiyah al-nafs dalam bentuk terapi jiwa didasari argument bahwa jiwa manusia dapat diobati. Upaya pengobatan penyakit jiwa mesti dilakukan melalui ilmu dan amal. Ilmu disini berfungsi untuk mengetahi sebab dan akibat suatu penyakit jiwa